2020
DOI: 10.3390/app10144767
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Grain Size Effects on Curvature in Micro-Extrusion

Abstract: The precision and accuracy of the final geometry in micro-parts is crucial, particularly for high-value-added metallic products. Micro-extrusion is one of the most promising processes for delivering high-precision micro-parts. The curving tendency observed in micro-extrusion parts is a major concern, significantly affecting the final part geometry. The purpose of this paper was to investigate the driving mechanism behind the curvature in micro-extrusion at room temperature. A finite element (FE) simulation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The FE results using an interface heat transfer coefficient of 2.5 kW/m • K were generally in good agreement with the experimental data. The coefficient used in the current study showed a similar order of magnitude, which is between 2.5 [9] and 7.5 k • W/m • K [26], to that in the literature. Figure 5 shows the effect of die shapes on the extrusion load.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The FE results using an interface heat transfer coefficient of 2.5 kW/m • K were generally in good agreement with the experimental data. The coefficient used in the current study showed a similar order of magnitude, which is between 2.5 [9] and 7.5 k • W/m • K [26], to that in the literature. Figure 5 shows the effect of die shapes on the extrusion load.…”
Section: Resultssupporting
confidence: 82%
“…However, high pressure is required to use various materials in this process. The porthole extrusion of soft materials such as aluminum [5][6][7][8][9][10] and magnesium [11,12] that are easy to deform and the extrusion of materials with high formability, such as steel [13,14], have been actively studied. However, studies on the tube extrusion of titanium are extremely rare due to the breakage of the dies due to high deformation resistance and the limitation of the equipment capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the curvature in the micro-extrusion significantly affected the final extrudates' geometry, which was caused by the grain size, grain boundary, grain orientation, and bearing length. For all conditions, the curvature of the micro-parts could be eliminated when the bearing length was greater than the exit diameter [28]. The extruded micro-gear rod was straightened in the experiments because the bearing length was approximately 1.6 times the exit diameter (Figure 4).…”
Section: Formed Micro-gear and Extrusion Force Of Different Holding T...mentioning
confidence: 99%
“…Fu et al [11,12] reported that the analysis of microforming can accurately predict the deformation behavior of the material by considering several influencing factors such as the flow pattern of the material, the state of the interface, and the flow stress curve. The author also reported the effects of microstructure, lubricant, and die coating on the forward-backward microextrusion technology of aluminum alloy [13][14][15]. The complex forward and backward material flow was evaluated by experiments and simulations, and it was proved that the backward extrusion was greatly affected by the friction between the die and the punch and microstructure.…”
Section: Introductionmentioning
confidence: 99%